Automated Generation of Three-Dimensional Complex Muscle Geometries for Use in Personalised Musculoskeletal Models - Modenese, Luca; Kohout, Josef (Annals of biomedical engineering, 2020)
The geometrical representation of muscles in computational models of the musculoskeletal system typically consists of a series of line segments. These muscle anatomies are based on measurements from a limited number of cadaveric studies that recently have been used as atlases for creating subject-specific models from medical images, so potentially restricting the options for personalisation and assessment of muscle geometrical models. To overcome this methodological limitation, we propose a novel, completely automated technique that, from a surface geometry of a skeletal muscle and its attachment areas, can generate an arbitrary number of lines of action (fibres) composed by a user-defined number of straight-line segments. These fibres can be included in standard musculoskeletal models and used in biomechanical simulations. This methodology was applied to the surfaces of four muscles surrounding the hip joint (iliacus, psoas, gluteus maximus and gluteus medius), segmented on magnetic resonance imaging scans from a cadaveric dataset, for which highly discretised muscle representations were created and used to simulate functional tasks. The fibres' moment arms were validated against measurements and models of the same muscles from the literature with promising outcomes. The proposed approach is expected to improve the anatomical representation of skeletal muscles in personalised biomechanical models and finite element applications.
Keywords: biomechanika; mrtvola; Muscle, Skeletal; lidé; magnetická rezonanční tomografie; Models, Biological; Hip Joint; Magnetic Resonance Imaging; počítačová rentgenová tomografie; Female; počítačové modelování podle konkrétního pacienta; Humans; Patient-Specific Modeling; biologické modely; Biomechanical Phenomena; ženské pohlaví; Aged, 80 and over; Tomography, X-Ray Computed; senioři nad 80 let; kosterní svaly; kyčelní kloub; Cadaver